Prenatal alcohol exposure and infant gross motor development: a prospective cohort study - Delyse Hutchinson; George J. Youssef; Clare McCormack; Judy Wilson; Steve Allsop; Jake Najman; Elizabeth Elliott; Lucinda Burns; Sue Jacobs; Ingrid Honan; Larissa Rossen; Hannah Fiedler; et al. (BMC, 2019)
Abstract Background Maternal alcohol consumption in pregnancy may have adverse effects on child gross motor (GM) development. There have been few human studies on this topic, particularly ones examining low exposure. This study examined the association between prenatal alcohol exposure (PAE) and infant GM development at 12-months of age. Methods Participants were 1324 women recruited from antenatal clinics in Sydney and Perth, Australia. Maternal and paternal alcohol use was assessed in pregnancy via interview; offspring GM development was measured at 12-months with the Bayley Scales of Infant Development (BSID-III). Results Any alcohol use in pregnancy was common: 56.1%, of pregnant women drank early in Trimester one (0-6 weeks), however this reduced to 27.9% on average thereafter and at predominantly low levels. However, infant BSID GM scale scores were not found to differ significantly as a function of PAE in the first 6-weeks (low, moderate, binge or heavy PAE), nor with low PAE across pregnancy. Conclusions We found no evidence to suggest that low PAE is associated with measurable impairment in infant GM development at 12-months. Further research is needed to examine potential PAE impacts on GM development in heavier exposure groups and through the childhood years when subtle GM deficits may be more detectable.